Survey on Efficient Certificateless Access Control for Wireless Body Area Networks (International Journal of Engineering and Computer Science, 2017)
Recent developments and advances in the field of wireless communication has led to the discovery of Wireless Body Area Networks (WBANs). The wearable computing devices made it easy to monitor the health issues of patients. The WBANs are widely used taking into account its numerous advantages. Many publications are available mentioning the various challenges of WBANs. In this paper, a survey is performed on the current state-of-art of WBANs based on the latest standards and publications. Open issues and challenges within each area are also explored as a source of inspiration towards future developments in WBANs